ANALISIS KAPASITAS DAYA DUKUNG PONDASI TIANG PANCANG DENGAN METODE US.ARMY CORPS - Aisah, Elpita (Jurnal Tekno Global, 2024)
ABSTRACT The bearing capacity of pile foundations is highly dependent on soil characteristics, materials, diameter, length, and installation methods. These factors affect the capacity of the pile to support the load, both from the capacity of the pile tip and the friction of the pile skin. The calculation of the bearing capacity of the foundation was carried out on the D.I. Lematang Irrigation gutter construction project in Pagar Alam City, especially on the foundation of the 3-channel gutter bridge of D.I. Lematang irrigation, to investigate whether the bearing capacity of the foundation can support the planned load or not because considering the main strength of a structure depends on its foundation, if the bearing capacity of the foundation is said to be safe, then undesirable things such as failure of the upper structure of the bridge gutter caused by foundation failure will not occur. The purpose of this study is to determine the value of the bearing capacity of the pile foundation that will be obtained to support the load above it. The calculation of the bearing capacity of the pile foundation is carried out using the U.S Army Corps method, the foundation is planned with a diameter of 1.4 m and a foundation depth of 16 m based on the Standard Penetration Test data in the calculation of the bearing capacity of the foundation, the ultimate bearing capacity value Qult is 36257.7684 kN, the permissible bearing capacity value Q all is 14503.107 kN for a single pile foundation, the number of piles is 18 with a distance of 5 m, for the efficiency value of the pile group is 1.028 and the bearing capacity of the pile foundation group Qall group is 268365.492 kN with a planned load of 265200 kN, meaning that the bearing capacity value of the pile group is greater than the planned load, meaning that this meets the requirements. Keywords: Foundation, Pile, Pile Carrying Capacity   ABSTRAK  Kapasitas dukung pondasi tiang sangat bergantung pada karakteristik tanah, bahan, diameter, Panjang,metode pemasangan. Faktor ini mempengaruhi kapasitas tiang dalam menopang beban, baik dari kapasitas ujung tiang maupun gesekan kulit tiang. Perhitungan daya dukung pondasi dilakukan pada proyek pembangunan talang air D.I Irigasi Lematang Kota Pagar Alam khususnya pada pondasi jembatan talang 3 saluran irigasi D.I Lematang, untuk menyelidiki apakah kapasitas daya dukung pondasi dapat menopang beban yang direncanakan atau tidak karena mengingat kekuatan utama pada suatu struktur tergantung pondasinya, jika kapasitas daya dukung pondasi dikatakan aman maka hal yang tidak diinginkan seperti kegagalan struktur atas talang jembatan yang disebabkan oleh kegagalan pondasi tidak akan terjadi . Tujuan dari penelitian ini adalah untuk mengetahui besarnya nilai kapasitas daya dukung pondasi tiang pancang yang akan didapatkan untuk menopang beban yang ada diatasnya. Perhitungan kapasitas daya dukung pondasi tiang pancang dilakukan dengan menggunakan metode U.S Army Corps, pondasi direncanakan dengan diameter sebesar 1,4 m dan kedalaman pondasi sedalam 16 m berdasarkan data Standart Penetration Test dalam perhitungan kapasitas daya dukung pondasi didapatkan nilai kapasitas daya dukung ultimit Q ult sebesar  36257,7684 kN, nilai kapasitas daya dukung izin Q all 14503,107 kN untuk pondasi tiang tunggal, didapatkan jumlah tiang sebanyak 18 buah dengan jarak 5 m, untuk nilai efesiensi kelompok tiang didapatkan 1,028 dan kapasitas daya dukung pondasi tiang pancang kelompok Qall kelompok didapatkan nilai sebesar 268365,492 kN dengan beban yang direncanakan 265200 kN artinya nilai kapasitas daya dukung kelmpok tiang lebih besar dari pada beban yang direncanakan, artinya hal ini memenuhi persyaratan. Kata Kunci: Pondasi ,Tiang Pancang, kapasitas Daya Dukung